(untitled) (Colloquia Comparativa Litterarum, 2025)
The article focuses on the slow entry of the term autofiction in Bulgarian literary critique. Our interest in this notion has been elicited initially by its large presence in French- and English-speaking critique from the end of the 20th century, and also by the fact that there are contemporary Bulgarian works that can be labelled as autofiction. Having appeared in the 1970s, the term demonstrates great vitality and has also been applied to works from previous periods. Similarly, even if it is just emerging in contemporary Bulgarian critique (the second half of 2010s and the early 2020s, mostly concerning works of Bulgarian authors published abroad and later translated into Bulgarian), it is applicable to earlier Bulgarian works. For the aims of the present study, we have analysed two novels: Vladimir Zarev’s Ruin (Разруха) (2004) and Zachary Karabashliev’s 18% Grey (2008).